Türkiye’nin Avrupa Birliği’ne Sürdürülebilir Katılımı İçin Düzenleyici Etki Analizinin Gerekliliği(Regulatory Impact Assessment Indispensable for Turkey’s Sustainable Accession to the European Union) - Sibel MEHTER AYKIN (Yönetim ve Ekonomi, 2010)
Despite the fact that regulatory impact assestment applications date back to 1990s in the OECD countries, it has not gained sufficient grounds in Turkey. Whereas, in the European Union, regulatory impact assessment is regarded as an important tool in decision making and policy formation process even in understanding the potential impacts of future accessions. In 2007, the Government declared Turkey’s acquis alignment programme in the framework of European Union and Turkish relations. The 2007-2013 programme requires a broad range of regulatory impact assesments to be done. By this way, sound grounds for transition period demands and derogations may be provided by Turkey. Furthermore, regulatory impact assessment enables all the stakeholders to manage the accession process effectively and efficiently on the basis of corporate responsibilty. Any acquis alignment programme, introduced without realizing relevant regulatory impact assessments, will be insufficient in achieving sustainability of Turkey’s accession to the EU. Thus, regulatory impact assessment as applied in the European Union should be studied in depth and realized.